Exposure to Rice Straw Ash Alters Survival, Development and Microbial Diversity in Amphibian Tadpoles - Qing Tong; Yue‐liang Pan; Qiu‐ru Fan; Wen‐jing Dong; Xin‐zhou Long; Ming‐da Xu; Li‐yong Cui; Zhi‐wen Luo (Ecology and Evolution, 2025)
ABSTRACT Amphibians are increasingly threatened by human activities, with rice straw burning emerging as a significant yet underexplored hazard. This practice may release harmful polycyclic aromatic hydrocarbons (PAHs), disrupt ecosystems, and affect amphibians. However, the impact on tadpole microbiota and development remains unclear. This study used scanning electron microscopy (SEM) and chemical analysis to characterize straw ash toxicity, assessed rice straw aqueous extracts of ash (AEA; 0, 0.75, 1.5, 3, and 6 g L−1) on Rana dybowskii tadpoles survival, growth, and development, and analyzed skin and gut microbiota via Illumina sequencing. Within the AEA, 10 varieties of PAHs exhibited higher quantities, including acenaphthylene, acenaphthene, and anthracene. SEM revealed irregular, porous, layered ash particles. Higher AEA concentrations reduced survival, delayed development, and affected body mass. The alpha diversity of both skin and gut microbiota significantly varied among groups. Beta diversity analyses indicated substantial shifts in microbial community structure with increased AEA concentrations. Linear discriminant analysis (LEfSe) identified microbial taxa enrichment and shifts, including the increase of potentially pathogenic genera such as Citrobacter and Yersinia in high‐concentration groups. BugBase analysis showed significant phenotypic changes in microbial communities. Our findings expose rice straw ash as a silent, global toxin that disrupts amphibian microbiota, growth, and survival—redefining routine straw burning as a planetary biodiversity hazard and urging immediate, sustainable reforms to protect wetland ecosystems.